Efeito do manejo de secagem e armazenamento sobre o valor nutritivo do feno de Crotalaria ochroleuca L. - Silva, Lurdes Rodrigues da (2022)
The haymaking process is a strategy adopted by some producers for forage conservation. Legume hay in the diet of ruminants is a form of food supplement with high nutritional value. Crotalaria ochroleuca L. (C. ochroleuca L.) is a forage legume used to control nematodes and its biomass has been used in green manure. An alternative is the use of this forage legume in the form of hay for animal feed. This study aimed to evaluate the influence of the legume drying management and storage time on the nutritional and sanitary quality of the hay. The experimental design was in randomized blocks, with plots divided in time, with 2 drying managements (with and without turning), 4 storage times (0, 30, 60 and 90 days of storage) and 4 replications. The parameters evaluated were: DM to determine the dehydration curve, chemical composition and digestibility, evaluation of the populations of microorganisms present in the hay, determining the CFU of bacteria (lactic acid bacteria, enterobacteria, Clostridium), fungi and yeasts. The cutting of the plants was performed at 123 DAG and the hay was baled 72 hours after cutting, with an average of 850 g kg-1 DM. Drying managements did not influence the DM content for the dehydration curve. The DM content of the forage for the dehydration curve showed a linear effect for the dehydration time and reached 848.7 g kg1 DM at 72 hours of drying. The hay storage time influenced (P < 0.001) the levels of DM, NDF, CP, hemicellulose, presenting a quadratic effect for the levels of DM, NDF and CP. The highest DM content of the hay was observed at 30 days (888.00 g kg-1), for the NDF content it was higher at 60 days (557.37 g Kg-1) and the CP content was higher at 90 days (204.64 g Kg1). The EE contents differed (P < 0.001) for the drying managements with and without turning (10.63 and 12.15 g kg-1) and storage time (with 13.46 g kg-1 DM at time zero), presenting decreasing linear effect during storage. There was no effect (P > 0.001) of management and storage time for ash, OM, ADF, LDA and cellulose contents. Drying managements and storage time did not influence (P > 0.001) on the in vitro digestibility of DM, IVDNDF and IVDOM. However, the highest IVOM was at 90 days (746 g Kg-1), IVOD was at 60 days (746 g Kg-1) and IVDNDF was at time zero (657 g Kg-1). The drying methods have not influenced the growth of bacteria in C. ochroleuca L. hay. There was an effect (P < 0.001) of the storage time on the growth of the bacterial population. Clostridium growth was higher at 60 days (7.16 log CFU g-1), with a quadratic response to hay storage time. The greatest growth of the Enterobacteriaceae population occurred at 30 days (6.42 log CFU g-1) with quadratic behavior in storage time. Lactic acid bacteria were present during storage, but have not differed (P>0.001) for storage time. Drying management using turning showed a fungal growth effect for Cladosporium (2.251 log CFU g-1). Based on the results obtained, it is recommended to use the drying management without turning the hay, as it has not influenced the nutritive value of the hay and requires less labor and use of equipment during drying. The hay can be used in animal feed, since the drying methods have not influenced the development of bacteria and the storage time influenced the development of bacteria, Clostridium, Enterobacteria and total bacteria, and it can be stored for up to 90 days, once which reduced the growth of these agents in this period. It is recommended to use drying management without turning over, seeing that in this study the use of turning management influenced the growth of the Cladosporium fungus during hay storage.